2013
DOI: 10.1007/s10059-013-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nucleolin as a Lipid-Raft-Dependent β1-Integrin-Interacting Protein in A375 Cell Migration

Abstract: Lipid rafts are related to cell surface receptor function. Integrin is a major surface receptor protein in cell adhesion and migration on the extracellular matrix (ECM). Here, we showed that lipid rafts played a critical role in human melanoma A375 cell spreading and migration on fibronectin; an important component of the ECM that interacts with β1 integrin. We found that the disruption of lipid rafts did not markedly inhibit the expression and activation of β1 integrin. By coimmunoprecipitation and mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Indeed, cell shape is drastically affected when NCL expression is reduced 27 29 . Many studies have shown that the expression of NCL is required for cell migration or adhesion 34 37 . In most of these studies, NCL silencing using siRNA reduced cell migration and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, cell shape is drastically affected when NCL expression is reduced 27 29 . Many studies have shown that the expression of NCL is required for cell migration or adhesion 34 37 . In most of these studies, NCL silencing using siRNA reduced cell migration and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Given that both integrin β1 and versican signaling have demonstrated dependence on lipid raft domains for their function 4, 16, 31, 32 , we also evaluated the effect of disrupting lipid rafts on the hyperalgesia induced by PGE 2 and CPA in the primed rat. The lipid raft disruptor methyl-β-cyclodextrin reversibly attenuated PGE 2 -, but not CPA-induced mechanical hyperalgesia in primed rats.…”
Section: Discussionmentioning
confidence: 99%
“…In interphase cells, regulation of microtubule dynamics is essential for numerous processes including cell architecture [ 34 ], intracellular trafficking and cell adhesion [ 35 , 36 ], cell polarization [ 37 ] and migration [ 38 ]. Interestingly, nucleolin has been associated to microtubule dependent intracellular trafficking [ 13 , 39 ] and has been implicated in cell adhesion and migration [ 9 , 12 , 40 ] It would be interesting to reevaluate the function of nucleolin in these processes by taking into account the involvement of nucleolin microtubule stabilization described herein. Indeed, in this report we show that nucleolin expression levels affect the different subpopulations of microtubules at the center and at the periphery of the cells ( Fig 4 ), arguing for a global role of nucleolin on microtubule dynamics independently of their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several functions of nucleolin have been described in the nucleoplasm, cytoplasm and at the cell membrane. Through its numerous sub cellular localizations and functions, nucleolin has been involved in the initiation and progression of lots of cancers [ 8 ] and more specifically in processes that could involve microtubules dynamics like cell adhesion and migration [ 9 12 ] as well as intracellular trafficking [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%